2020
DOI: 10.1021/jacs.9b11507
|View full text |Cite
|
Sign up to set email alerts
|

Oriented External Electric Fields and Ionic Additives Elicit Catalysis and Mechanistic Crossover in Oxidative Addition Reactions

Abstract: Judiciously applied oriented external electric fields (OEEFs) exert catalytic effects on the kinetics and improve the thermodynamics of chemical reactions. Herein, we examine the ability of OEEFs to assist catalysts and show that the rate of oxidative addition between palladium catalysts and alkyl/aryl electrophiles can be controlled by an OEEF applied along the direction of electron reorganization (the "reaction axis"). The concerted mechanism of oxidative addition proceeds through a transition state with mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 108 publications
4
106
0
Order By: Relevance
“…(equivalent to 1.0 to −1.0 V Å −1 ) and the results are shown in Figure 5. These field values are typically used in theoretical mechanistic crossover studies [61] and experimentally observed in vibrational Stark effect studies [62] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(equivalent to 1.0 to −1.0 V Å −1 ) and the results are shown in Figure 5. These field values are typically used in theoretical mechanistic crossover studies [61] and experimentally observed in vibrational Stark effect studies [62] …”
Section: Resultsmentioning
confidence: 99%
“…(equivalent to 1.0 to À1.0 V À1 )and the results are showni nF igure 5. These field values are typically used in theoretical mechanistic crossover studies [61] and experimentally observed in vibrational Stark effect studies. [62] The redox potential (E8), electron-transfer rate constants (log k e ), and barrier (E act )a re fairly constant at moderate field strengthsa long the y axis and change only at relatively high field values (> 0.5 V À1 ,F igure 5a nd Figure S6 in the Supporting Information).…”
Section: Relativeindependence Of Metal-ion-induced Cyp450 Activation mentioning
confidence: 99%
“…Consequently, the geometric and electronic modification of cisplatin under different oriented external electric fields (OEEFs) has been detailedly studied in this work. It is recently reported that OEEFs can cause structural distortions, 18,19 induce proton transfer, 20,21 modulate NLO responses of materials, 22,23 and catalyze various reactions as smart catalysts and controllers of reaction mechanisms 24–33 . Herein, we will mainly focus on the following two questions: (a) What is the influence of OEEFs on the geometric and electronic structure of cisplatin?…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that OEEFs can cause structural distortions, 18,19 induce proton transfer, 20,21 modulate NLO responses of materials, 22,23 and catalyze various reactions as smart catalysts and controllers of reaction mechanisms. [24][25][26][27][28][29][30][31][32][33] Herein, we will mainly focus on the following two questions: (a) What is the influence of OEEFs on the geometric and electronic structure of cisplatin? (b) How does the OEEF-induced geometric and electronic modification improve the antitumor activity of cisplatin in electrochemotherapy?…”
mentioning
confidence: 99%
“…[6a, 14] Such throughspace models are beginning to supersede earlier empirically derived models of aromatic interactions, [15] and numerous investigations have highlighted the importance of field effects in enzyme-catalyzed reactions [16] and synthetic organic chemistry. [17] However,c ontrasting with the success of empirically derived Hammett substituent constants in accounting for reactivity in aw ide range of contexts,h igh-quality experimental data quantifying through-space substituent effects are surprisingly limited.…”
Section: Introductionmentioning
confidence: 99%